2013
DOI: 10.2134/agronj2012.0218
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Risk from Reducing Nitrogen Fertilization Using Hierarchical Models and On‐Farm Data

Abstract: Current systems for developing N recommendations for corn (Zea mays L.) lack methods to quantify the effects of factors influencing yield responses to N and quantify the uncertainty in N recommendations. We utilized hierarchical modeling and Bayesian analysis to quantify the risk from reducing N to corn using on‐farm observations. Across Iowa, farmers conducted 34 trials in 2006 and 22 trials in 2007. Each trial had a farmer’s normal N rate alternating with a reduced rate (by about 30% less) in three or more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…A typical adaptive management method to obtain robust evaluations of N management at the field level to fine-tune N practices is to perform replicated strip trials comparing either two or more rates of N or different forms, timing or placement of N. Two treatment replicated strip trials, usually the farmer N rate or an N rate from a recommendation system like the yield goal system or the MRTN system, and a rate that is 45 kg N ha -1 greater or less than the farmer or recommendation system rate, enable farmers to refine N recommendations (Kyveryga et al, 2013). Refinement of N recommendations on an individual field basis is clearly needed for all recommendation systems based on the information provided throughout this paper.…”
Section: Adaptive Managementmentioning
confidence: 99%
“…A typical adaptive management method to obtain robust evaluations of N management at the field level to fine-tune N practices is to perform replicated strip trials comparing either two or more rates of N or different forms, timing or placement of N. Two treatment replicated strip trials, usually the farmer N rate or an N rate from a recommendation system like the yield goal system or the MRTN system, and a rate that is 45 kg N ha -1 greater or less than the farmer or recommendation system rate, enable farmers to refine N recommendations (Kyveryga et al, 2013). Refinement of N recommendations on an individual field basis is clearly needed for all recommendation systems based on the information provided throughout this paper.…”
Section: Adaptive Managementmentioning
confidence: 99%
“…In our study, the general hierarchical model comprised three levels: data, field, and regional (Kyveryga et al 2013). The data model included a distribution of YR values (YR nj ) within a trial (where n = 1,…,N), for an individual grid cell (where j = 1,…,M) to be normally distributed with a mean l n and a precision k n unique for that trial.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…All calculations were done using the statistical software R (R Development Core Team 2009). More details for using Hierarchical models and Bayesian statistics to analyze data collected from OETs can be found in Kyveryga et al (2013).…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In that way, in Belgium, farmers used to provide N in sufficient and reasonable quantities (60 kg N ha À1 ) at the tiller, stem extension, and flag leaf stages, which relate to Zadok stages 23, 30, and 39, respectively. In recent studies, Dumont et al (2014aDumont et al ( , 2014cDumont et al ( , 2015b successfully transposed the theory of yield distribution analysis (Day, 1965;Kyveryga et al, 2013) onto the study of crop model simulations. They demonstrated that the probability of achieving yields greater than the mean of the corresponding distribution was the highest when Belgian farmers' most typical N rate was applied.…”
Section: Numerical Nitrogen Managementmentioning
confidence: 99%